Financial access and productivity of manufacturing firms in the Philippines - Catacutan, Zandro M. (Journal of Management, Economics, and Industrial Organization, 2022)
Many scholars examined and immensely found significant causal relationship present between access to finance and firms’ productivity. However, limited studies and inconclusive generalizations are still pervasive regarding co-existing nexus between financial access in form of overdraft facilities offered by financial institutions toward productivity of manufacturing firms in the Philippines. In addition, cross-country differences related to business environment, income levels, size and depth of the financial system, financial frictions and legal constraints potentially exposing model estimations to simultaneity issues. Thus, this study extends the empirical examination of finance-led productivity growth assumptions and expands the application of econometric modelling through instrumental variable regression models using an enterprise survey conducted in 2015 by the World Bank among selected manufacturing firms in the Philippines. The main findings revealed the positive and significant impact of financial access through acquisition of overdraft facilities in enhancing manufacturing firms’ productivity proxied by real annual sales. Meanwhile, other firm-related factors such as R&D and capital intensities were also found to have significant influence on productivity of manufacturing firms. These results signal practical implications highlighting managers consideration in the inclusion of overdraft facilities as an alternative source of funding for their financing strategies alongside proper resource allocation and management of technology and capital structure, which will provide an avenue for firms to achieve the desired level of productivity growth. However, lack of empirical evidence was found regarding the significant contribution of financial access on productivity when proxied by measures of TFP.